2012
DOI: 10.1139/w2012-035
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of class 1 integrons among enteropathogenicEscherichia coli

Abstract: The aim of this study was to investigate the incidence of and resistance gene content of class 1 integrons among enteropathogenic Escherichia coli (EPEC) and non-EPEC and to investigate intraspecies genetic diversity of EPEC strains isolated from children with diarrhea in Iran. Twenty-eight EPEC and 16 non-EPEC strains isolated from children with diarrhea were tested for the presence of a class 1 integron associated integrase gene (int1). Sequence analysis was performed to identify the resistance gene content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Similar array of gene cassettes of class I integrons was primarily detected among enteric bacteria including Proteus, E. coli and Shigella spp. (Eftekhari et al, 2013;Hussein et al, 2009;Najibi et al, 2012). Moreover, comparable array of gene cassettes have been detected in Klebsiella pneumonia and UPEC (Lee et al, 2001).This may reveal the fact that the Enterobacteriaceae act as a reservoir of resistance genes that can be transferred to other species within or outside the family and alter the genetic contents and resistance potential in bacteria (Young and Amyes, 1986).…”
Section: Discussionmentioning
confidence: 90%
“…Similar array of gene cassettes of class I integrons was primarily detected among enteric bacteria including Proteus, E. coli and Shigella spp. (Eftekhari et al, 2013;Hussein et al, 2009;Najibi et al, 2012). Moreover, comparable array of gene cassettes have been detected in Klebsiella pneumonia and UPEC (Lee et al, 2001).This may reveal the fact that the Enterobacteriaceae act as a reservoir of resistance genes that can be transferred to other species within or outside the family and alter the genetic contents and resistance potential in bacteria (Young and Amyes, 1986).…”
Section: Discussionmentioning
confidence: 90%
“…Four classes of integrons have been reported up to now, and the class I integrons are more commonly recognized among clinical isolates [ 21 , 30 ]. Several studies have shown the widespread distribution of integrons among enteric bacteria from different countries including Iran [ 12 , 16 , 19 , 25 , 26 , 28 ].…”
mentioning
confidence: 99%
“…sonnei , and S. enterica isolates were nearly identical, suggesting that probably these different species have similar mechanisms for attainment of MDR. All of these results together with earlier finding of the extremely efficient interspecies transfer of integron-carrying elements, illustrated that horizontal transfer of integron-carrying elements plays a dominant role in the development of MDR among members of Enterobacteriaceae , independent of species or origin of isolation (10). …”
Section: Discussionmentioning
confidence: 56%